An annotated checklist of Malachiidae (Coleoptera: Cleroidea) from Iran - Mirutenko, Vladyslav; Ghahari, Hassan (Zootaxa, 2016)
A checklist of Iranian Malachiidae (Coleoptera) is given in this paper. Eighty two species from 22 genera (subfamily Malachiinae) are listed in the fauna of Iran. Of these species, 31 are endemic to Iran, and one Anthocomus pupillatus Abeille de Perrin, 1890 is a new record for this country.